Trends and health impacts of major urban air pollutants in Kazakhstan. (1st November 2020) - Kerimray, Aiymgul; Assanov, Daulet; Kenessov, Bulat; Karaca, Ferhat
ABSTRACT: The air quality in cities in Kazakhstan has been poorly investigated despite the worsening conditions. This study evaluates national air pollution monitoring network data (Total Suspended Particle-TSP, NO2, SO2, and O3 ) from Kazakhstan cities and provides estimates of excess mortality rates associated with PM2.5 exposure using the Global Exposure Mortality Model (GEMM) concentration-response function. Morbidity rates associated with PM10 exposure were also estimated. Annual average (2015-2017) population-weighted concentrations were Kazakhstan cities was 157, 51, 29, and 41 μg m −3 for TSP, NO2, SO2, and O3 respectively. We estimated a total of 8134 adult deaths per year attributable to PM2.5 (average over 2015–2017) in the selected 21 cities of Kazakhstan. The leading causes of death were ischemic heart disease (4080), stroke (1613), lower respiratory infections (662), chronic obstructive pulmonary disease (434), lung cancer (332). The per capita mortality rate attributable to ambient air pollution (per 10 5 adults per year) was less than 150 in nine cities, between 150 and 204 in nine cities, and between 276 and 373 in three industrial cities (Zhezkazgan, Temirtau, and Balkhash). Implications : Quantitative information on the health impacts of air pollution can be useful for decision-makers in Kazakhstan to justify environmental policies and identify policy and funding priorities for addressing air pollution issues. This information can also be useful for policymakers by improving the quality of government-funded environmental reports and strategic documents, as they have many shortcomings in terms of the selection of air quality indicators, identification of priority pollutants, and identification of sources of pollution. This study has high significance due to the lack of data and knowledge in Central Asia, especially Kazakhstan.